Keanekaragaman dan Kemerataan Spesies Anggota Ordo Anura di Lereng Selatan Gunung Merapi Tahun 2012 - Donan Satria Yudha; Yonathan Yonathan; Rury Eprilurahman; Septiana Indriawan; Eka Cahyaningrum (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Merapi volcano as one of national park is an ecotourism site which is very potential to visit. Information about species diversity for a national park is very important especially if its area fluctuated susceptibly. Two years after 2010 Merapi eruption, there are no research about species diversity and evenness of Anuran in that place. The research is carried out during June-November 2012 which is dry season. The objective of this research is to study the species diversity and evenness of Anuran in southern slope of Mount Merapi. The research is carried out in 6 locations; those are Kali Kuning, Telogo Muncar, Telogo Nirmolo, Petak Pitu, Bukit Turgo, and Bukit Plawangan. We used Visual Encounter Survey (VES) method combined with transect in Kali Kuning, Telogo Muncar, and Petak Pitu. VES method combined with time search in Telogo Nirmolo and Bukit Turgo. VES method combined with track exploration in Bukit Plawangan. Species diversity is analyzed with Shanon-Wiener diversity index. Species evenness is analyzed with Pielou evenness index. Total individuals each species is counted to know species abundance. Species diversity of anuran in southern slope of Mount Merapi is consisted of 12 species’ which is distributed in 6 locations. The highest diversity and evenness of anuran is at Bukit Turgo (H’=1.31; E=0.94). The lowest diversity and evenness of anuran is at Petak Pitu (H’=0.49; E=0.3). Species diversity of anuran in southern slope of Mount Merapi is low (Bukit Turgo and Kali Kuning) and very low (Bukit Plawangan, Telogo Muncar, Telogo Nirmolo, and Petak Pitu). Species evenness of anuran in southern slope of Mount Merapi is stable (Telogo Nirmolo and Bukit Turgo), still labil (Bukit Plawangan, Kali Kuning, and Telogo Muncar), and oppressed (Petak Pitu).